ANALISIS MISKONSEPSI SISWA BERKEMAMPUAN AKADEMIK TINGGI DAN RENDAH PADA MATERI SISTEM REPRODUKSI MANUSIA KELAS XI DI SMA NEGERI 1 YOSOWILANGUN LUMAJANG TAHUN AJARAN 2025/2026 - Unzila Nur Fadilah; Ira Nurmawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze students’ misconceptions on the topic of the human reproductive system based on academic ability categories using a diagnostic three-tier test instrument. The human reproductive system is considered one of the complex topics in biology, which often leads to misconceptions among students. Misconceptions can hinder students’ understanding of advanced concepts because students possess understandings that are inconsistent with scientific concepts. This research was conducted at SMAN 1 Yosowilangun Lumajang by grouping students into high and low academic ability categories based on the results of the first tier in the three-tier test. The three-tier instrument was chosen because it is capable of identifying students’ answers, reasoning, and confidence levels, thereby distinguishing students who understand concepts, experience misconceptions, and do not understand concepts. Preliminary observations indicated that students still experienced difficulties in understanding the concepts of the human reproductive system, particularly fertilization, reproductive hormones, spermatogenesis, and oogenesis. This study is expected to provide an overview of the characteristics of students’ misconceptions in each academic ability category and serve as a consideration for teachers in determining more appropriate learning strategies and remedial efforts to improve students’ conceptual understanding.